2012
DOI: 10.1177/0038038511422551
|View full text |Cite
|
Sign up to set email alerts
|

Calling for Care: ‘Disembodied’ Work, Teleoperators and Older People Living at Home

Abstract: The provision of 'distant' care to older people living at home through telecare technologies is often contrasted negatively to hands-on, face-to-face care: telecare is seen as a loss of care, a dehumanization. Here we challenge this view, arguing that teleoperators in telecare services do provide care to older people, often at significant emotional cost to themselves. Based on a European Commission-funded ethnographic study of two English telecare monitoring centres, we argue that telecare is not 'disembodied'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 21 publications
6
77
0
6
Order By: Relevance
“…Staff end up giving out lots of advice and find themselves, as a consequence, undertaking various forms of 'emotional labour' (fieldwork extracts 10-12). As Roberts et al (2012) observe, telecare services are providing more than just 'disembodied care'.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Staff end up giving out lots of advice and find themselves, as a consequence, undertaking various forms of 'emotional labour' (fieldwork extracts 10-12). As Roberts et al (2012) observe, telecare services are providing more than just 'disembodied care'.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of telecare call centre work have shown how the use of the technology becomes interwoven with existing social networks and hands-on care, shaping the meaning of care and the role of call takers (Pols 2010;Pols and Willems 2011;Milligan et al 2011;Roberts et al 2012). The EFORTT project illustrated how call takers undertake a variety of complex tasks in their efforts to ensure that older people benefit.…”
Section: Assisted Living Technologies and Servicesmentioning
confidence: 99%
See 3 more Smart Citations